2019
DOI: 10.1111/ggi.13768
|View full text |Cite
|
Sign up to set email alerts
|

SARC‐F: A validation study with community‐dwelling older Japanese adults

Abstract: Aim The SARC‐F is a useful clinical index for sarcopenia screening; however, this measure has low sensitivity. Furthermore, this tool has never been validated on community‐dwelling older Japanese adults. The goal of the present study was to validate a Japanese version of the SARC‐F and confirm its suitability for Japanese samples. Methods Participants were 734 community‐dwelling older adults in the Itabashi Ward, Japan. Bioimpedance measures, walking speed, grip strength and instrumental activities of daily li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
6
24
1
1
Order By: Relevance
“…In the present study, high sensitivity and specificity of SARC-F were observed (92.9% and 98.1%, respectively), which proves that the tool detects cases with no sarcopenia and identifies individuals with sarcopenia. Similar specificity values were reported by Woo et al (98.7% for men, and 94.4% for women), 24 Kera et al (97.3%) 25 and Kim et al (91.2%). 26 However, the sensitivity values in the present study were very high as compared to the abovementioned authors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, high sensitivity and specificity of SARC-F were observed (92.9% and 98.1%, respectively), which proves that the tool detects cases with no sarcopenia and identifies individuals with sarcopenia. Similar specificity values were reported by Woo et al (98.7% for men, and 94.4% for women), 24 Kera et al (97.3%) 25 and Kim et al (91.2%). 26 However, the sensitivity values in the present study were very high as compared to the abovementioned authors.…”
Section: Discussionsupporting
confidence: 87%
“…SARC-F was originally developed in English but EWGSOP2 recommends for it to be translated and validated into other languages as well. SARC-F has already been translated into Brazilian Portuguese, 27 Chinese, 28 Japanese, 25 Korean, 26 Mexican Spanish, 11 and numerous other language validations in Europe are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of some previous studies, we have demonstrated a correlation between SARC-F and some parameters associated with sarcopenia, such as age, low gait speed, low upper and lower limb strength, and low ALM [19,20,24]. Similarly to the findings of Kera et al [19], we have observed a correlation between SARC-F results and the ability to perform basic and instrumental activities of daily living (assessed with Katz and Lawton Scales). Based on our analysis, the Polish version of the SARC-F showed adequate validity as a diagnostic tool for sarcopenia.…”
Section: Reliability and Validitysupporting
confidence: 92%
“…In 2019, Sanchez-Rodriguez et al published similar results (Cronbach's alpha 0.779) for the Spanish version of SARC-F [16]. In contrast, insufficient internal consistency (Cronbach's alpha below the threshold 0.65) was found for the Japanese version of the SARC-F and the version translated into Spanish and culturally adapted for the Mexican population (Cronbach's alpha 0.610 and 0.641, respectively [19,20].…”
Section: Reliability and Validitymentioning
confidence: 97%
See 1 more Smart Citation